PENGARUH STRATEGICONTEXTUAL TEACHING AND LEARNING (CTL)BERBANTUAN MEDIA KARTU TERHADAP HASIL BELAJARMATEMATIKA SISWA KELAS IVSD SWASTA MUHAMMADIYAH 3 PADANGSIDIMPUAN - Lubis, Jumaita Nopriani; Juliana, Rina; Dalimunthe, Rahma Yasrah; Agustini, Rini; Ayurani, Isma; Yuisman, Dedi; Rumondang, Riski; Rodiyah, Nurul Isatun (Fakultas Keguruan Dan Ilmu Pendidikan, UM-Tapsel, 2023)
This study aims to determine the effect of the contextual teaching and learning (CTL) strategy assisted by card media on the learning outcomes of fourth grade students at Muhammadiyah 3 Padangsidimpuan Private Elementary School. This study used quantitative research with a pre-experimental design method, type one group pretest-posttest (preliminary test, final test of a single group). The population in the study were all fourth grade studentswhich totaled 66 people. The sample in this study was class IV-A, which consisted of 3 people. The test instrument used to find out the resultsstudent learning is an essay test in the form of pretest and posttest.The results of hypothesis testing using the Wilcoxon test, the sig. of 0.000. Because the value of sig. 0.000 is less than <0.05, it can be concluded that